High-normal free thyroxine level is related with decreased bone mineral density in nonobese male patients with type 2 diabetes over 50 years old - Hanxin Zhao; Dike Shi; Guoxing Wang; Yu Ruan; Xiaocheng Feng; ChengFang Jia; Qingqing Wang; Xuehong Dong (Therapeutic Advances in Chronic Disease, 2023)
Background: The prevalence of ‘low bone mineral density (BMD)’ in Type 2 diabetes (T2DM), especially stratified by body mass index, is seldom reported. The relation of the euthyroid range and low BMD in T2DM remains to be further elucidated. Objectives: We aim to investigate the thyroid hormones’ impact on BMD among euthyroid patients with T2DM. Design and methods: A total of 1452 hospitalized T2DM patients with normal thyroid function (43.6% males aged over 50 and 56.4% postmenopausal females) were enrolled in this cross-sectional study. BMD was measured at lumbar spine by GE lunar dual-energy X-ray absorptiometry system, and ‘low BMD’ was defined as T -score <−1.0 SD. The prevalence of ‘low BMD’ was compared between obese and nonobese (body mass index < 25 kg/m 2 ) groups for both sexes, and the relation of low BMD and free T4 quartiles was explored by multiple logistic regression. Results: The general prevalence of ‘low BMD’ was 12.3% for male patients aged over 50 (15.5% in the nonobese group and 8.0% in the obese group) and 49.8% for postmenopausal females (56.7% in the nonobese group and 48.9% in the obese group). After adjustment in multiple linear regression, free T4 level remained significantly related to decreased BMD in nonobese male subgroup. Multiple logistic regression revealed that BMD of the highest free T4 quartile (1.12–1.48 ng/dL) decreased significantly than other three quartiles after adjusting for confounding factors including age, body mass index, serum calcium and creatinine level, fasting glucose, alkaline phosphatase, glycosylated hemoglobin, total cholesterol, and smoking history (OR = 2.724, 95% CI = 1.085–6.840, p  = 0.033). No significant relation was found in obese male or postmenopausal female groups. Conclusion: High-normal free T4 is a potential independent risk factor for ‘low BMD’ in nonobese male T2DM patients aged over 50. Close attention should be paid to thyroid function profile, even within normal range, in nonobese men with underlying higher fracture risks on diabetes status.